Bridging the gap: an integrated paediatric to adult clinical service for young adults with kidney failure. (1st June 2012) - Harden, P N; Walsh, G; Bandler, N; Bradley, S; Lonsdale, D; Taylor, J; Marks, S D
Abstract : Problem Transition from paediatric to adult care of young adults with chronic diseases is poorly coordinated, often delayed, and usually managed through a single referral letter. About 35% of young adults lose a successfully functioning kidney transplant within 36 months of transfer from paediatric to adult services. Design Before and after study of the impact of a new integrated paediatric-adult clinical service for patients with kidney failure. Setting Adult renal centre in Oxford and two paediatric renal centres in London. Strategies for change An integrated paediatric-young adult joint transition clinic and care pathway was established in 2006, in conjunction with a young adult clinical service with regular community based clinics. Previously, young adult transplant recipients were transferred by a single referral letter to an adult renal consultant and managed in a conventional adult clinic. Key measures for improvement Rates of acute rejection and loss of kidney transplants five years before and five years after the introduction of the integrated young adult care pathway. Effects of the change Nine young adult kidney transplant recipients were transferred directly to adult care between 2000 and 2006 (group 1). From 2006 to 2010, 12 young adult transplant recipients underwent integrated transition into the new young adult service (group 2). Six transplants were lost in group 1 (67%) compared with no transplant losses in group 2. Lessons learnt Implementing an integrated transition clinic, coupled with improving young adults' healthcare experience through a young adult clinic, improved patient adherence to regular medication and engagement with healthcare providers, as judged by reduced transplant failure rates. This model may be applicable to other young adult populations with chronic disease transferring to adult healthcare.